Study on improving thermal and compatibility behavior of gypsum PLA/stearic-lauric acid composite as phase change material - Nurhanifa Aidy; Rozanna Dewi; Azhari Azhari; Teuku Rihayat; Aida Safitri; Adi Saputra Ismy (Jurnal POLIMESIN, 2021)
Commercial buildings, one of which is for hospitality, consumes a large amount of energy. The energy needs are generally dominated by lighting systems, domestic hot water systems and air conditioning systems. Energy consumption in commercial buildings and residential use of 35.3% of the total global energy use. The aim of this study is to investigate thermal properties and chemical compatibility of PCM based eutectic fatty acid (lauric-stearic) combined with polylactic acid in the pores of the gypsum that was established using the vacuum impregnation method. The procedure ensures that pla 1.5% and 2% with Lauric-Stearic (LA-SA) are mixed evenly, compared with pure gypsum and LA-SA addition. Based on TGA test  specific lauric acid and stearic acid heat analysis was performed in the modulated tga mode between 90.34oC and 369.51oC. The degradation material decreased significantly at -3.404 mg. Sample mixed between Poly lactid acid, eutectic fatty acid and gypsum  contain hydroxyl groups with significant absorptions for ft-ir analysis. The bonded oxygen-hydrogen stretching vibrations of lactid acids and gypsum,  range between 2000 and 3000 cm-1. Similarly, alcohols exhibit similar shapes at higher wavenumbers ranging from 3230 to 3550 cm-1.